Tecnologías de la información para resolver contingencias en la afiliación al régimen subsidiado de salud en Perú: "Resuelve tu afiliación" - Villegas-Ortega, José (2016)
The National Health Authority (SUSALUD) has developed an online platform, "ReSUelve tu afiliación", with the intent to solve the problems with health service access experienced by Peruvian citizens who hold health insurance policies through institutions that manage health insurance funds (IAFAS). This platform virtually articulates the main IAFAS in Peru, which receives requests from any user requiring an update on his/her affiliation status to be resolved within 24 hours. Nearly 8 months after the implementation of this platform, more than 55 thousand applications have been resolved, thus ensuring timely access to health services under the corresponding user coverage form. As a result, this platform has helped to guarantee citizens' rights to health service access in the face of infringement caused by delays in affiliation processing among the different IAFAS in Peru.